2022
DOI: 10.1088/1361-6463/ac99e9
|View full text |Cite
|
Sign up to set email alerts
|

Normally-OFF AlGaN/GaN-based HEMTs with decreasingly graded AlGaN cap layer

Abstract: In this work, an E-mode AlGaN/GaN-based HEMTs with a graded AlGaN cap layer (GACL) is proposed and numerically studied by Silvaco TCAD. The GACL is designed with a decreasingly graded Al composition x along [0001] direction and the initial x is smaller than the Al composition of the Al0.2Ga0.8N barrier layer (BL). This GACL scheme can simultaneously produce high-concentration polarization-induced holes and negative net polarization charges at the GACL/BL interface. This can facilitate the separation of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…The numerical investigations in this study were carried out by technology computer-aided design simulation provided by Silvaco International [20]. The key models employed in the device simulation include the parallel electric field model for velocity saturation, Fermi-Dirac statistics model (FERMI), Shockley-Read-Hall model (SRH), Auger-Recombination model (AUGER), the Albrecht model (ALBRCT.N) and the polarization models (POLARIZATION and CALC.STRAIN for spontaneous polarization and piezoelectric polarization, respectively) [14].…”
Section: Device Structures and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical investigations in this study were carried out by technology computer-aided design simulation provided by Silvaco International [20]. The key models employed in the device simulation include the parallel electric field model for velocity saturation, Fermi-Dirac statistics model (FERMI), Shockley-Read-Hall model (SRH), Auger-Recombination model (AUGER), the Albrecht model (ALBRCT.N) and the polarization models (POLARIZATION and CALC.STRAIN for spontaneous polarization and piezoelectric polarization, respectively) [14].…”
Section: Device Structures and Modelsmentioning
confidence: 99%
“…However, the performance trade-off among output current (I DS ), threshold voltage (V TH ), and breakdown voltage (V BD ) of the P-HEMTs still needs to be tackled at the moment. To be specific, the high Mg doping and larger hole concentration (N A ) in the p-GaN cap is required to achieve a large V TH of the P-HEMT [14,15]. The higher N A , on the other hand, would lead to a lower I DS , degraded gate reliability, and early device breakdown [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The key models employed in the simulation include Shockley-Read-Hall model, Fermi-Dirac model, polarization models (POLARIZATION and CALC. STRAIN for spontaneous polarization and piezoelectric polarization, respectively), Auger recombination (AUGER), and constant low-field mobility model [32,33]. In order to well match the actual device characteristics, based on previous reports, the simulation parameters are set as follows: the gate metal work function of 4.8 eV [19]; the Al 2 O 3 relative dielectric constant of 9.3; the specific Ohmic contact resistance (ρ C ) of 1.4 × 10 −4 Ω•cm 2 for all devices, same as the value reported in [34].…”
Section: Physical Models Used In Tcad Simulationmentioning
confidence: 99%
“…They are essentially suitable for various applications targeting low losses and high operating frequencies and temperatures. This special issue evaluates a series of GaN-and AlGaN-based electronic devices proposed by Chinese researchers, such as Schottky barrier diodes (SBDs) [19], metal-oxide-semiconductor field effect transistors (MOSFETs) [20], high electron mobility transistors (HEMTs) [21][22][23][24][25], and so forth.…”
Section: Electronic Devicesmentioning
confidence: 99%
“…They found that, at low temperatures, the device's threshold voltage shifts positively, and both maximum transconductance and ON-resistance significantly improve. Furthermore, Xing et al [23] demonstrated an E-mode AlGaN/GaN HEMT with a graded AlGaN cap layer (GACL). In their work, the threshold voltage of gradient AlGaN gate metal semiconductor HEMT rose to 4 V, proving that 80 nm GACL metal semiconductor HEMT was the best structure.…”
Section: Electronic Devicesmentioning
confidence: 99%